2007
DOI: 10.1002/jez.389
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a biotelemetric technique, using ambulatory miniature black globe thermometers, to quantify thermoregulatory behaviour in ungulates

Abstract: Behavioural thermoregulation is an animal's primary defence against changes in the thermal environment. We aimed to validate a remote technique to quantify the thermal environment behaviourally selected by free-ranging ungulates. First, we demonstrated that the temperature of miniature, 30 mm diameter, black globes (miniglobes) could be converted to standard, 150 mm diameter, black globe temperatures. Miniglobe temperature sensors subsequently were fitted to collars on three free-ranging ungulates, namely blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 30 publications
1
42
0
Order By: Relevance
“…Through the use of biologgers to detect microclimate selection without human observers, we also have shown that Arabian oryx selected cooler microclimates with increasing environmental temperatures (Fig. 3) [91], and at times accessed microclimates with a black globe temperature (which integrates the effects of air temperature, radiation, and wind speed; [92]) as much as 12°C below that of the open environment. In dry periods in which the oryx had no access to drinking water, they selected cooler microclimates than they did at the same environmental heat load in wetter periods, when they had access to drinking water [91].…”
Section: Behavioural Adjustmentsmentioning
confidence: 81%
“…Through the use of biologgers to detect microclimate selection without human observers, we also have shown that Arabian oryx selected cooler microclimates with increasing environmental temperatures (Fig. 3) [91], and at times accessed microclimates with a black globe temperature (which integrates the effects of air temperature, radiation, and wind speed; [92]) as much as 12°C below that of the open environment. In dry periods in which the oryx had no access to drinking water, they selected cooler microclimates than they did at the same environmental heat load in wetter periods, when they had access to drinking water [91].…”
Section: Behavioural Adjustmentsmentioning
confidence: 81%
“…4.3 ± 0.2) and oryx (upper right panel, y = 0.85 ± 0.006x ? 3.5 ± 0.2), indicating the selection of cooler microclimates during this period J Comp Physiol B (2012) 182:437-449 445 were able to detect the selection of cooler microclimates without observers present, by using miniature globe thermometers attached to collars, a novel technique we developed for recording microclimate selection by freeliving animals (Hetem et al 2007). There was no difference in the pattern of microclimate selection by the two species, consistent with them being stationary and in the shade during the hottest times of the day.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to a tracking radio transmitter, the collar supported a miniature black globe thermometer (''miniglobe''), to allow for the dynamic ambulatory measurement of the microclimate that each animal chose to occupy. This technique has been validated previously on other ungulate species (Hetem et al 2007). Miniglobe temperature was measured by a small temperature-sensitive data logger (see below) inserted into the centre of a matt-black hollow copper sphere (30 mm diameter, Press Spinning and Stamping Co., Cape Town, South Africa).…”
Section: Surgerymentioning
confidence: 99%
“…Each collar supported a miniature black globe thermometer ('miniglobe'), which allowed for the dynamic measurement of the microclimate that the goat chose to occupy. This technique has proven successful on other ungulate species (Hetem et al, 2007). Miniglobe temperature was measured by a small temperature-sensitive data logger (see temperature measurements) inserted into the center of a matt-black hollow brass sphere (30-mm diameter; Press Spinning & Stamping Co., Cape Town, South Africa).…”
Section: Surgerymentioning
confidence: 99%